REGULASI PENATAAN PASAR MODERN DAN REVITALISASI PASAR TRADISIONAL DI KOTA BLITAR - Wydha Mustika Maharani (Universitas Islam Balitar, 2019)
The development of a modern market and shopping centers more quickly in Indonesia could no longer avoid. The development of this phenomenon indirectly can threaten the traditional markets. To anticipate, envy and social unrest then required regulation which control modern market and required an apparent attempt to maintain and develop traditional markets in the revitalization of traditional markets. This research aims to: (1) knowledge and describe regulations modern markets that already exist, but in its implementation regulations modern markets are not aligned with the existing especially in relation to the distance between modern markets and traditional markets. (2) knowledge and describe revitalization program traditional markets to protect traditional markets in order to compete with modern market. This research adopted qualitative descriptive approaches. The research results show that the dualistic economic between a modern market with traditional markets made difficult the collaboration between them.